A Compartive analysis of Resource allocation Algorithm For Energy Consumption - Shubhangi Dharmendra Gunjal , Yogesh Kumar Sharma , Satish Ramchandra Todmal (International Journal of Advanced Science and Technology, 2020)
Wireless Sensor network is a small node array that gathers and transmits the information to be processed. Nonetheless, data becomes useful if their location becomes identified and resources can be distributed to different locations so that power demand can be lowered. The network of nodes is multi-hop. In either direction, every node can move freely. We can use wireless devices such as mobile, PDA, tablet, Laptop etc. anywhere at any time. The area of WSN localization and resource allocation is a developing rapidly by extensive research work. This location resource allocation information can be achieved using different localization and resource allocation techniques in WSN. The location of events taken place can be determined by knowing the location of sensor nodes and how much resources available. This paper extensively reviews different localization and resource allocation techniques basic and improved its nodes energy consumption in WSN and also presents some parameter based comparative study. This work includes the PSO method for optimization, so WSN required less energy. This study is valuable for better understanding of existing methods and improved ones, with the help of this can develop other advanced techniques. This work presents a detailed survey on different localization and resource allocation techniques and solutions to routing protocol.